Immunization status in chronic obstructive pulmonary disease: A multicenter study from Turkey - Ozlu, Tevfik; Bulbul, Yilmaz; Aydin, Derya; Tatar, Dursun; Kuyucu, Tulin; Erboy, Fatma; Nizam, M. (Wolters Kluwer Medknow Publications, 2019)
OBJECTIVE: The purpose of this study is to detect the prevalence and the factors associated with influenza and pneumococcal vaccination and outcomes of vaccination during 2013-2014 season in patients with chronic obstructive pulmonary disease (COPD) in Turkey. METHODS: This was a multicenter retrospective cohort study performed in 53 different centers in Turkey. RESULTS: During the study period, 4968 patients were included. COPD was staged as GOLD 1-2-3-4 in 9.0%, 42.8%, 35.0%, and 13.2% of the patients, respectively. Influenza vaccination rate in the previous year was 37.9%; and pneumococcus vaccination rate, at least once during in a life time, was 13.3%. Patients with older age, higher level of education, more severe COPD, and comorbidities, ex-smokers, and patients residing in urban areas had higher rates of influenza vaccination. Multivariate logistic regression analysis showed that advanced age, higher education levels, presence of comorbidities, higher COPD stages, and exacerbation rates were associated with both influenza and pneumococcal vaccination. The number of annual physician/outpatient visits and hospitalizations due to COPD exacerbation was 2.73 +/- 2.85 and 0.92 +/- 1.58 per year, respectively. Patients with older age, lower education levels, more severe COPD, comorbid diseases, and lower body mass index and patients who are male and are residing in rural areas and vaccinated for influenza had significantly higher rates of COPD exacerbation. CONCLUSIONS: The rates of influenza and pneumococcal vaccination in COPD patients were quite low, and the number of annual physician/outpatient visits and hospitalizations due to COPD exacerbation was high in Turkey. Advanced age, higher education levels, comorbidities, and higher COPD stages were associated with both influenza and pneumococcal vaccination.
Keywords: Chronic obstructive pulmonary disease; chronic obstructive pulmonary disease exacerbation; influenza vaccine; pneumococcal vaccine